PEREKONOMIAN NEGARA DAN KETANAGAKERJAAN - ., Pitoyo (KYBERNAN: Jurnal Ilmiah Ilmu Pemerintahan, 2010)
The basic conception of Indonesia economy is togetherness or gotong royong. Production is done by all people and for the sake of all people prosperity. If not so management will be held by individual and people will be depressed. The suitable form of such an enterprise is cooperatives. In the mean time globalization attack the fundamental principle of the Indonesia economy which lead to maket economy. The big capital play a big role behind the globalization and that is, no doubt capitalism. His aim is Indonesian shall stay as consumer in which imported goods and services are cheaper than domestic product. At the last ten years influence of globalization to Indonesia economy is more intense and its result is proverty and unemployment increase. Beyond that, political affairs worsens the economy, democratic practices including human rights issues bear social conflicts, the credibility of government decreases. It is therefore to cope with such a situation a summit tripartite cooperation is needed very urgently. Close cooperation amongst employers, workers an government who actually producing goods and services should be sat together to decide how much production of goods an services should be done according to the demand ofgoods and services of the people. This is the task of the government to influence with public policy in the economy to elevate poverty and unemployment. Reluctance to those efforts law and order are hardly to implement. On the contrary market mechanism continue to set new equlibrium by increasing prices without taking care of values contained in the state fundamental philosophy pancasila